The Effect of Supervised Exercise Therapy on Physical Activity and Ambulatory Activities in Patients with Intermittent Claudication. Issue 2 (February 2015) - Fokkenrood, H.J.P.; Lauret, G.J.; Verhofstad, N.; Bendermacher, B.L.W.; Scheltinga, M.R.M.; Teijink, J.A.W.
<x xml:space="preserve">Abstract</x> Objective/Background Intermittent claudication (IC) is associated with a reduction in physical activity (PA) and a more rapid functional decline leading to a higher mortality rate compared with healthy individuals. Supervised exercise therapy (SET) is known to increase the walking capacity of patients with IC. However, it is unclear whether SET increases PA. The aim of this study was to investigate the effect of SET on PA levels and ambulatory activities in patients with IC. Methods Patients newly diagnosed with IC were requested to wear an activity monitor 1 week prior to and 1 week immediately after 3 months of SET. The primary outcome was the percentage of patients meeting the minimum recommendations of PA (American College of Sports Medicine [ACSM]/American Heart Association [AHA] recommendation for public health of ≥ 67 metabolic equivalents [METs]/min/day, in bouts of ≥ 10 min) at baseline and after 3 months of SET. Additionally, daily PA level (METs/min), duration of ambulatory activities, daily number of steps, pain free walking distance (PFWD), maximal walking distance (MWD), and Short Form Health Survey (SF-36) health surveys were compared before and after SET. Results Data from 41 participants were available for analysis. A higher number of participants met the ACSM minimum recommendation for PA at the 3 month follow up (baseline: 43%; 3 months: 63%; p = .003). Despite significant increases in PFWD (baseline: 210 m; 3 months: 390 m; p = .001), MWD (baseline: 373 m; 3 months: 555 m; p = .002) and physical functioning score (SF-36) following SET, no increase in the mean daily PA level was found (395 ± 220 vs. 411 ± 228 METs/min; p = .43). Furthermore, the total number of steps and time spent in ambulatory activities did not change following SET. Conclusion Three months of SET for IC leads to more patients meeting the ACSM/AHA public health minimum recommendations for PA. Assessment of PA could be incorporated as an outcome parameter in future research comparing different treatment modalities for peripheral arterial disease.